Drosophila Homolog of FMRP Maintains Genome Integrity by Interacting with Piwi. Issue 1 (20th January 2016) - Jiang, Fangfang; Lu, Falong; Li, Peixue; Liu, Wei; Zhao, Lu; Wang, Qifu; Cao, Xiaofeng; Zhang, Lei; Zhang, Yong Q.
Abstract: Fragile X syndrome (FraX), the most common form of inherited mental retardation, is caused by the absence of the evolutionally conserved fragile X mental retardation protein (FMRP). While neuronal functions of FMRP have been intensively studied for the last two decades, its role in non-neuronal cells remains poorly understood. Piwi, a key component of the Piwi-interacting RNA (piRNA) pathway, plays an essential role in germline development. In the present study, we report that similar to piwi, dfmr1, the Drosophila homolog of human FMR1, is required for transposon suppression in the germlines. Genetic analyses showed that dfmr1 and piwi act synergistically in heterochromatic silencing, and in inhibiting the differentiation of primordial germline cells and transposon expression. Northern analyses showed that roo piRNA expression levels are reduced in dfmr1 mutant ovaries, suggesting a role of dfmr1 in piRNA biogenesis. Biochemical analysis demonstrated a physical interaction between dFMRP and Piwi via their N-termini. Taken together, we propose that dFMRP cooperates with Piwi in maintaining genome integrity by regulating heterochromatic silencing in somatic cells and suppressing transposon activity via the piRNA pathway in germlines.